Morphological and Physiological Stress Responses of Lettuce to Different Intensities of Continuous Light - Zha, Lingyan; Liu, Wenke; Zhang, Yubin; Zhou, Chengbo; Shao, Mingjie (Frontiers in Plant Science, 2019)
In this study, specific dynamic changes in growth, oxidative stress, ascorbate metabolism, and chlorophyll fluorescence were monitored during 12 days in lettuce plants exposed to continuous light (CL) of different intensities: low light (LL, 100 μmol·m-2·s-1), medium light (ML, 200 μmol·m-2·s-1), and high light (HL, 300 μmol·m-2·s-1). Lettuce plants grown under CL of higher light intensity gained greater biomass, dry weight ratio, root/shoot ratio, and specific leaf FW, but not leaf area. Both the reactive oxygen species (ROS) production and the lipid peroxidation degree, measured in terms of the malondialdehyde (MDA) levels, were progressively enhanced by increasing the light intensity of CL. Overall, the pool sizes of ascorbate (AsA) and glutathione, as well as the activities of enzymes involved in AsA metabolism, had positive correlations with light intensity under CL. Ascorbate peroxidase and dehydroascorbate reductase presented the maximal and minimal responses to light intensity, respectively, among all the studied enzymes. After 6 days under CL, ML and HL intensity caused reversible photoinhibition, represented by lower values of maximum quantum efficiency (Fv/Fm), effective quantum yield (ΦPSII), and photochemical quenching (qP) and a higher value of non-photochemical quenching (qN). However, this photoinhibition recovered on day 12 with increasing of Fv/Fm, ΦPSII, and qP. Taken together, under ML and HL conditions, greater AsA level could help maintain photosynthetic efficiency by elevating excess excitation energy dissipation, though ROS accumulation and lipid peroxidation could not be prevented in the long-term. Likewise, there was no dark period under LL condition, but no photooxidative stress was observed in lettuce. Thus, it is concluded that photooxidative stress induced by CL can be attributed to excessive daily light integral instead of circadian asynchrony.